Dampak Tuberkulosis Paru Terhadap Perkembangan Fisik dan Kognitif Anak di Puskesmas Sematang Borang Kota Palembang: Penelitian - Sherly Widianti; Zakiah Yusema Dhesim Barra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Pulmonary tuberculosis (pulmonary TB) is a chronic infectious disease that not only affects the respiratory system, but can also interfere with children's growth and development. TB infection in children is at risk of causing physical growth disorders such as decreased weight and height, as well as delayed cognitive development. This study aims to analyze the impact of pulmonary tuberculosis on the physical and cognitive development of children at the Sematang Borang Community Health Center, Palembang City. This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 28 children diagnosed with pulmonary TB and met the inclusion criteria. Data were collected through observation and questionnaires, then analyzed univariately using the SPSS version 25 program. The results showed that the average age of respondents was 10.32 years. The average weight was 28.72 kg and height was 132.29 cm. All respondents were confirmed to have pulmonary TB (100%). The average cognitive development score was 1.75, indicating that most children were in the "starting to develop" category. This finding indicates that pulmonary TB has an impact on the decline in nutritional status and delays in cognitive development in children. Pulmonary TB has a real impact on the physical and cognitive development of children.